Gait Retraining From Rearfoot Strike to Forefoot Strike does not change Running Economy - Roper, Jenevieve Lynn; Doerfler, Deborah; Kravitz, Len; Dufek, Janet S.; Mermier, Christine (International Journal of Sports Medicine, 2017)
Gait retraining is a method for management of patellofemoral pain, which is a common ailment among recreational runners. The present study investigated the effects of gait retraining from rearfoot strike to forefoot strike on running economy, heart rate, and respiratory exchange ratio immediately post-retraining and one-month post-retraining in recreational runners with patellofemoral pain. Knee pain was also measured. Sixteen participants (n=16) were randomly placed in the control (n=8) or experimental (n=8) group. A 10-minute treadmill RE test was performed by all subjects. The experimental group performed eight gait retraining running sessions where foot strike pattern was switched from rearfoot strike to forefoot strike, while the control group received no intervention. There were no significant differences for running economy (p=0.26), respiratory exchange ratio (p=0.258), or heart rate (p=0.248) between the groups. Knee pain reported on a visual analog scale was also significantly reduced (p<0.05) as a result of retraining. The present study demonstrates that retraining from rearfoot strike to forefoot strike did not affect running economy up to one-month post-retraining while reducing running-related patellofemoral pain.
Keywords: foot strike pattern; knee pain; leg; oxygen consumption